2018
DOI: 10.1038/s41598-018-34676-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Hepatic Toxicity after Repeated Stereotactic Body Radiation Therapy for Recurrent Hepatocellular Carcinoma using Deformable Image Registration

Abstract: This study aimed to evaluate hepatic toxicity after repeated stereotactic body radiation therapy (SBRT) for recurrent hepatocellular carcinoma (HCC) using deformable image registration (DIR). Between January 2007 and December 2015, 85 patients who underwent two sessions of SBRT for HCC treatment were retrospectively analyzed. A DIR technique was used to calculate the cumulative dose of the first and second SBRT to the normal liver by matching two computed tomography simulation images. The Dice similarity coeff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 35 publications
0
15
1
Order By: Relevance
“…Their obtained probability distributions of the expected OS were nearly identical with 6.452 and 6.371 years in the RFA and SBRT groups, respectively. Recently, Lee et al reported that repeated SBRT for recurrent HCC could be safely performed with acceptable hepatic toxicity [24]. These results encouraged the use of SBRT as a comparable treatment to RFA for RHCC after RFA.…”
Section: Discussionmentioning
confidence: 99%
“…Their obtained probability distributions of the expected OS were nearly identical with 6.452 and 6.371 years in the RFA and SBRT groups, respectively. Recently, Lee et al reported that repeated SBRT for recurrent HCC could be safely performed with acceptable hepatic toxicity [24]. These results encouraged the use of SBRT as a comparable treatment to RFA for RHCC after RFA.…”
Section: Discussionmentioning
confidence: 99%
“…In regards to this issue, some retrospective studies published in recent years have reported that repeated SBRT for recurrent HCC was safely performed with acceptable hepatic toxicity. [41][42][43] In order to clarify long-term liver toxicities of both treatments, prospective studies in larger numbers of patients are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that frequent intrahepatic recurrences of HCC require repeated treatments, SBRT might be spared for lesions unsuitable for other liver-directed treatments. In contrast, Lee et al [32] reported the treatment outcomes after a repeated SBRT for recurrent HCCs with a median tumor size of 1.7 cm (interquartile range, 1.4–2.2 cm) in 85 patients. The 3-year local control rates were not different between the first and second SBRT (94.9% vs. 90.4%, p =0.667).…”
Section: Clinical Considerationsmentioning
confidence: 99%
“…Biliary stricture has been occasionally reported at the rate of 0–3% [12,28,32,46-48]. Eriguchi et al [49] found biliary stenosis in 2 out of 50 patients irradiated with over 20 Gy to the central biliary system; 1 patient experienced biliary stricture at the area irradiated with >80 Gy after the second SBRT and the stenotic site of the other patient was outside the area irradiated with >20 Gy.…”
Section: Toxicities After Stereotactic Body Radiotherapymentioning
confidence: 99%